Exploring Evaluation Competency Amongst Public Health Nurses in Canada: A Scoping and Document Review - McKay, Kelly (Université d'Ottawa / University of Ottawa, 2022)
This study sought to better understand program evaluation capacity and competency amongst public health nurses. Program evaluation plays a vital role in public health and is an identified core competency for public health practice (Canadian Public Health Agency). In Part One, I conducted a scoping review to systematically map the current literature on this topic and to identify important areas for future research. Twenty-three articles were selected based on pre-established exclusion and inclusion criteria and the assistance of a secondary reviewer. The articles highlighted the value of program evaluation in public health and its importance as a nursing skill amidst the evolving health care sector. Themes identified included: a broader lack of public health competencies (including program evaluation) among all public health professionals; the complexities and challenges of evaluating public health interventions; and the uncertainty of what constitutes adequate evaluation competency in public health. Furthermore, my review noted inconsistent terminology to describe a public health nurse and the need for further exploration around the specific evaluation capacity of public health nurses. In Part Two, I explored the stated or expected evaluation competencies for public health nurses through a document review of relevant Canadian public health nursing core competencies, guidelines, and standards for practice. The identification of 52 stated evaluation competencies, demonstrates the assumption that public health nurses have competency and or capacity related to program evaluation and contrasts with the themes identified in my scoping review. Furthermore, the documents I reviewed included no specific reference to the Canadian Evaluation Society (CES), however some of the included content did align with the CES Program Evaluation Standards. This study demonstrates a misalignment between the discourse in the literature reviewed related to evaluation competency amongst public health nurses and the stated or assumed evaluation competencies put forth in leading public health nursing documentation. In the absence of any standardized evaluation training and preparation for public health nurses, further exploration is needed around what these broad evaluation competencies mean in practice and how they can be objectively assessed, exhibited, and better integrated into public health nursing education and evaluation capacity building activities. These questions warrant further investigation to ensure public health interventions are properly evaluated and that public health nurses have the competencies required for effective public health practice.
Keywords: public health nurses; public health professionals; program evaluation competency; program evaluation capacity; scoping review